2015
DOI: 10.1039/c4sc03549f
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous silica nanoparticles for 19F magnetic resonance imaging, fluorescence imaging, and drug delivery

Abstract: We described perfluorocarbon encapsulated in mesoporous silica nanoparticles which enabled dual modal imaging (NIR/19F MRI) and drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
146
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(150 citation statements)
references
References 37 publications
3
146
1
Order By: Relevance
“…A complete list of peptides used in this study can be found in Figure S1 B) Disordered peptide design showing 19 F sources alternating with positive charge causing a random-coil through electrostatic repulsion. C) Select fluorinated molecules used for 19 F MRI: i) Perfluoro-15-crown-5 ether [6] ii) Perfluoro(polyethylene glycol) methyl ether [13] and iii) PERFECTA. [14] …”
Section: Figurementioning
confidence: 99%
“…A complete list of peptides used in this study can be found in Figure S1 B) Disordered peptide design showing 19 F sources alternating with positive charge causing a random-coil through electrostatic repulsion. C) Select fluorinated molecules used for 19 F MRI: i) Perfluoro-15-crown-5 ether [6] ii) Perfluoro(polyethylene glycol) methyl ether [13] and iii) PERFECTA. [14] …”
Section: Figurementioning
confidence: 99%
“…Nakamura et al . 38 reported a PFC core-shell MSN called mFLAME filled with PFCE for drug delivery. The mFLAME particles were modified with different surface ligands which allowed for dual mode detection using 19 F-MRI and fluorescence microscopy.…”
mentioning
confidence: 99%
“…To reduce often observed clustering and aggregating of the AuNRs without CTAB, the surface of AuNRs is often modified with mesoporous silica or all kinds of polymers [6,7]. And the large specific surface area of mesoporous silica and polymers guarantees the large loading capacity [8][9][10]. Nevertheless, the performance of these modified nanocapsules is not as good as initially envisioned.…”
Section: Introductionmentioning
confidence: 96%